2010
DOI: 10.1103/physrevc.81.064904
|View full text |Cite
|
Sign up to set email alerts
|

Inclusiveπ0,η, and direct photon production at high transverse momentum inp+p

Abstract: We report a measurement of high-p T inclusive π 0 , η, and direct photon production in p + p and d + Au collisions at √ s NN = 200 GeV at midrapidity (0 < η < 1). Photons from the decay π 0 → γ γ were detected in the barrel electromagnetic calorimeter of the STAR experiment at the Relativistic Heavy Ion Collider. The η → γ γ decay was also observed and constituted the first η measurement by STAR. The first direct photon cross-section measurement by STAR is also presented; the signal was extracted statistically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 78 publications
(108 reference statements)
3
13
0
Order By: Relevance
“…energy √ s, these data provide constraints only for momentum fractions x 0.01, and the gluons are constrained only indirectly via scale-evolution effects and momentum sum rule [12]. To obtain better gluon constraints, the potential of inclusive pion production in d+Au collisions at RHIC [13][14][15][16] was first discussed in ref. [17] and eventually the data were incorporated into the global fits [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…energy √ s, these data provide constraints only for momentum fractions x 0.01, and the gluons are constrained only indirectly via scale-evolution effects and momentum sum rule [12]. To obtain better gluon constraints, the potential of inclusive pion production in d+Au collisions at RHIC [13][14][15][16] was first discussed in ref. [17] and eventually the data were incorporated into the global fits [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Both the observations at lower and higher M inv are now shown to be related to the jet fragmentation, where the effects at lower and higher M inv are then related to the near-and away-side jet structures, respectively. A qualitatively similar effect at low M inv was already seen in studies at RHIC [169], but the jet correlations observed were significantly weaker than what is found at LHC energy. The ratios of the energy asymmetry α and opening angle ψ are also individually much closer to unity.…”
Section: Diphoton Pairs From Same and Different Ancestorssupporting
confidence: 83%
“…Along with the precise data from the Large Hadron Collider (LHC), the list of data types that are included in state-of-the-art PDF analyses has grown, now ranging from traditional inclusive deeply-inelastic scattering to jet, top-quark and heavy gauge-boson production [2,3]. At this moment, global fits of proton PDFs do not use any data from the Relativistic Heavy-Ion Collider (RHIC), and nuclear-PDF fits [4,5] use only inclusive pion data from RHIC [6,7]. The advantage of the lower center-of-mass (c.m.)…”
Section: Introductionmentioning
confidence: 99%